Essays on Applied Economics - Saberianranjbar, Fatemeh (Université d'Ottawa / University of Ottawa, 2018)
Chapter 1. In the 1970s, competition policy in the United States banking sector changed from exempting competition to liberalization and deregulation. Competition not only plays an important role in allocational efficiency but it is also essential for long-term economic growth. This chapter develops a model of banking contributions to evaluate to what extent banks affect the level of competition in the banking sector, and tests the model's predictions using a novel detailed dataset which includes all contributions made by banks from 1993 to 2010 in the United States. Controlling for banks' characteristics, the results are consistent with the model's predictions and show show that a higher level of contributions increases the Lerner index (as a measure of competition) or in the other words, decreases the level of competition. Chapter 2. This chapter provides the first empirical evidence that market structure affects the electoral power of firms as special interest groups. Firms not only affect the election outcomes by making contributions to their preferred candidates, they also enforce social norms among their members by encouraging them to vote for the candidate with the most closely-aligned interests. This chapter uses a linear probability model to analyze 574 open-seat races for the House of Representatives in the United States between 1990 and 2014. The results show that, even when controlling for the total value of contributions made to a candidate, political donations made by firms with high market power have a positive effect on the candidates' probability of winning. The findings are consistent with the idea from collective action theory that concentrated industries are more likely to behave as an organized interest group to advance their interests. Chapter 3. Ethnic heterogeneity is an important factor in the formation of human sexual network and the prevalence of STDs. Racial and ethnic ties create closed social networks with rigid in-group boundaries and hampers the intra-group dissemination of information. Slow information flow among groups facilitates the spread of STDs by encouraging individuals to ethnically diversify their sexual partners in order to lower the chance of getting caught cheating. Analyzing a cross-province sample of 39,830 sexually active adults driven from the 2013-2014 Canadian Community Health Survey, we find that individuals who live in a highly ethnically diversified neighbourhood are more susceptible to STDs compared to ones who live in a ethnically homogenous neighbourhood. Evidence from several robustness checks suggests that the relationship is causal.
Keywords: Applied Economics; Political Economics; Health Economics; Campaign Contributions; Lobbying